ASSESSMENT OF THE HEALTH STATUS OF PROFOUNDLY PREMATURE INFANTS IN INFANCY - Yuldasheva G.G; Toshpulatova G.O (Western European Studies, 2024)
Young children are the object of close attention, as they constitute a high-risk group in terms of morbidity and mortality. This scientific article presents the results of assessing the health status of deeply premature infants in the first year of life. It has been found that in the first year of life, profoundly premature children are most often sick with acute respiratory viral infections (up to 8 episodes per year), pneumonia (41% of children), perinatal encephalopathies (59,8%), accompanied by lag in neuropsychiatric (90,4%) and physical development (57%). Retinopathy also occurs in 29% of patients.
Keywords: premature infants; retinopathy; pneumonia